Radiolabeled Dendrimer Coated Nanoparticles for Radionuclide Imaging and Therapy: A Systematic Review - Miriam Conte; Maria Silvia De Feo; Marko Magdi Abdou Sidrak; Ferdinando Corica; Joana Gorica; Luca Filippi; Orazio Schillaci; Giuseppe De Vincentis; Viviana Frantellizzi (MDPI AG, 2023)
Background: Dendrimers are nanoscale-size polymers with a globular structure. They are composed of an internal core and branching dendrons with surface active groups which can be functionalized for medical applications. Different complexes have been developed for imaging and therapeutic purposes. This systematic review aims to summarize the development of newer dendrimers for oncological applications in nuclear medicine. Methods: An online literature search was conducted on Pubmed, Scopus, Medline, Cochrane Library, and Web Of Science databases selecting published studies from January 1999 to December 2022. The accepted studies considered the synthesis of dendrimer complexes for oncological nuclear medicine imaging and therapy. Results: 111 articles were identified; 69 articles were excluded because they did not satisfy the selection criteria. Thus, nine duplicate records were removed. The remaining 33 articles were included and selected for quality assessment. Conclusion: Nanomedicine has led researchers to create novel nanocarriers with high affinity for the target. Dendrimers represent feasible imaging probes and therapeutic agents since, through the functionalization of external chemical groups and thanks to the possibility to carry pharmaceuticals, it can be possible to exploit different therapeutic strategies and develop a useful weapon for oncological treatments.